Restoring Natural Killer Cell Immunity against Multiple Myeloma in the Era of New Drugs - Pittari, Gianfranco; Vago, Luca; Festuccia, Moreno; Bonini, Chiara; Mudawi, Deena; Giaccone, Luisa; Bruno, Benedetto (Frontiers in Immunology, 2017)
Transformed plasma cells in multiple myeloma (MM) are susceptible to natural killer (NK) cell-mediated killing via engagement of tumor ligands for NK activating receptors or “missing-self” recognition. Similar to other cancers, MM targets may elude NK cell immunosurveillance by reprogramming tumor microenvironment and editing cell surface antigen repertoire. Along disease continuum, these effects collectively result in a progressive decline of NK cell immunity, a phenomenon increasingly recognized as a critical determinant of MM progression. In recent years, unprecedented efforts in drug development and experimental research have brought about emergence of novel therapeutic interventions with the potential to override MM-induced NK cell immunosuppression. These NK-cell enhancing treatment strategies may be identified in two major groups: (1) immunomodulatory biologics and small molecules, namely immune checkpoint inhibitors, therapeutic antibodies, lenalidomide and IDO inhibitors; (2) NK cell therapy, namely adoptive transfer of unmanipulated and CAR-engineered NK cells. Here, we summarize the mechanisms responsible for NK cell functional suppression in the context of cancer and, specifically, myeloma. Subsequently, contemporary strategies potentially able to reverse NK dysfunction in MM are discussed.